INVESTIGATING USER PERCEPTIONS OF AI TECHNOLOGY AND ITS ETHICAL IMPLICATIONS ON EMPLOYMENT DYNAMICS AND BIAS - Saleh Ahmed Jalal Siam; Mubashshir Bin Mahbub (Acta Informatica Malaysia)
The rapid advancement of Artificial Intelligence (AI) technology has catalyzed significant transformations across various sectors, notably impacting employment dynamics and raising concerns about bias and fairness. This qualitative research aims to delve into user perceptions regarding AI technology and its ethical implications on employment dynamics and bias. Through in-depth interviews and thematic analysis, this study explores the multifaceted dimensions of how users perceive AI’s impact on employment patterns, potential biases embedded within AI systems, and the ethical considerations surrounding its implementation. Findings suggest a complex interplay between technological advancements, societal values, and ethical dilemmas, underscoring the need for comprehensive policies and frameworks to address emerging challenges. By shedding light on user perspectives, this research contributes to a deeper understanding of the ethical implications of AI technology on employment dynamics and bias.